PERANCANGAAN TOOLS PENGUKURAN KINERJA PERUSAHAAN DAN KARYAWAN DENGAN MENGGUNAKAN OBJECTIVE MATRIX - Winda Amilia (AGROINTEK, 2013)
Performance measurement is a management tool to improve the decisionmaking quality for organizational performance improvement. Performance managementis about how to manage activities within an organization to achieve its goals. Theperformance measurement design requires performance indicators formed from thedimensions of satisfaction and employee contributions to the company. By using thedimensions of employee satisfaction structured business goals to be achieved throughthe fulfillment of employee satisfaction firm. Business objectives is the basis for buildKey Performance Indicators in this measurement design. Based on the results of theKPIs identification, there are 12 KPIs to measure corporate performance to theemployee. The results shown on OMAX that 4 KPIs on the highest target, and 8 KPIs are stillunder target. Measurement results compiled in Objective Matrix (OMAX) to determinethe level / achievement level performance indicators set targets.